Improving sustainability of beef industry supply chains. Issue 6 (6th June 2016) - Goddard, Ellen; Boaitey, Albert; Hailu, Getu; Poon, Kenneth
Abstract : Purpose: – The purpose of this paper is to evaluate cow-calf producer incentive to adopt innovations in traits with important environmental and economic implications for the beef supply chain. Design/methodology/approach: – A whole farm multi-year farm optimization model that tracks changes in discounted net returns and methane emissions from the use of newer DNA-related technologies to breed for feed efficient cattle is developed. The analysis is situated within the context of whole beef cattle supply chain. This allows for the derivation of the entire value and environmental impact of the innovation, and the decomposition of value by different participants. The impact of different policies that can stimulate producer uptake and the diffusion of the innovation is also addressed. Findings: – The results of the study showed that whilst the use of the breeding technology yielded positive economic and environmental benefits to all producers in the supply chain, primary adopters were unlikely to adopt. This paper finds evidence of the misalignment in incentives within the supply chain with a significant proportion of the additional value going to producers who do not incur any additional cost from the adoption of the innovation. The study also highlighted the role of both public and market-based mechanisms in the innovation diffusion process. Originality/value: – This paper is unique as it is the first study that addresses producer incentive to adopt genomic selection for feed efficiency across the entire beef cattle supply chain, and incorporates both economic and environmental outcomes.